2023
DOI: 10.3390/biom13081205
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Interaction between the Neurosteroid (3α,5α)3-Hydroxypregnan-20-One (3α,5α-THP) and the Mu-Opioid System Activation during Forced Swim Stress in Rats

Giorgia Boero,
Minna H. McFarland,
Ryan E. Tyler
et al.

Abstract: The neurosteroid 3α,5α-THP is a potent GABAA receptor-positive modulator and its regulatory action on the HPA axis stress response has been reported in numerous preclinical and clinical studies. We previously demonstrated that 3α,5α-THP down-regulation of HPA axis activity during stress is sex-, brain region- and stressor-dependent. In this study, we observed a deleterious submersion behavior in response to 3α,5α-THP (15 mg/kg) during forced swim stress (FSS) that led us to investigate how 3α,5α-THP might affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Moreover, several studies have shown that neuroactive steroids may increase alcohol reinforcement, consumption, and reinstatement of drinking in animal models of alcohol addiction, depending on the dose [48,[507][508][509][510]. A recent study also unveiled a possible deleterious interaction between allopregnanolone administration and opioid system activation during forced swim stress in rats [511]. This result suggests the need for further studies to address potential limitations of allopregnanolone for psychiatric disorders involving HPA axis activation.…”
Section: Constraints and Potential Side Effects Of Neurosteroid Therapymentioning
confidence: 98%
“…Moreover, several studies have shown that neuroactive steroids may increase alcohol reinforcement, consumption, and reinstatement of drinking in animal models of alcohol addiction, depending on the dose [48,[507][508][509][510]. A recent study also unveiled a possible deleterious interaction between allopregnanolone administration and opioid system activation during forced swim stress in rats [511]. This result suggests the need for further studies to address potential limitations of allopregnanolone for psychiatric disorders involving HPA axis activation.…”
Section: Constraints and Potential Side Effects Of Neurosteroid Therapymentioning
confidence: 98%